(untitled) (The International Journal for Scientific Research, 2024)
This study examines the impact of artificial intelligence (AI) on the future of digital media, detailing the evolution of AI technologies and their implications for the media industry. It also explores the benefits and challenges faced by media professionals due to the integration of AI technologies. The study highlights that information technology is contributing to the formation of a new digital environment, where applications based on human intelligence lead to the emergence of new concepts and values in media. Amid rapid technological advancements, the utilization of AI in the media industry is significant for enhancing content quality and streamlining production processes. However, these technologies also raise questions about the future of public relations and the integration of creative media. The study employed a comprehensive research methodology, utilizing contemporary books, academic theses, and related scientific studies, along with the internet for data collection. The study emphasizes that AI technologies play a crucial role in advancing the media industry, improving content quality, and accelerating production speed. However, humans should remain the primary drivers of these technologies, and it is essential to establish new ethical standards to ensure a balance between humans and machines in media production. Among the research recommendations: the need for journalists and media professionals to pay attention to artificial intelligence technologies to improve the quality of content and simplify production processes.